Is Life an Unavoidable Consequence of the Formation of the Universe? Investigating the Formation of Bio-Precursors and the Signature of Earth-Like Living Forms - Gomez de Castro, Ana I. (Frontiers in Astronomy and Space Sciences, 2018)
TThis contribution to the Research Topic "Imagining the Future of Astronomy and Space Sciences" focuses on astrobiology and exoplanetary research. Understanding the origin of life is the main scientific challenge to this century and an interdisciplinary endeavor in itself. To that astronomy will contribute in three key issues. Firstly, by measuring the abundance of elements relevant to life in the Universe. Then by determining the preferred location for aminoacids and complex organic molecules assembly. Finally, by investigating the signatures of life in exoplanets. A new generation of facilities will need to be built to address these questions. The relevance of ultraviolet instrumentation for this purpose is highlighted in this short perspective.